SAT0331 Comparison of Anatomic Knee Alignment on Physical Examination and Radiographs. (23rd January 2014) - Hemmati, I.; Sayre, E. C.; Guermazi, A.; Nicolaou, S.; Kopec, J. A.; Thorne, A.; Singer, J.; Cibere, J.
Abstract : Background: Severity of knee malalignment is a risk factor for osteoarthritis (OA) progression. Currently the hip-knee-angle, assessed on a full-limb radiograph, is the gold standard. Direct measurement of the anatomic axis using standard knee radiographs has been validated as an alternative method (1 ). Objectives: The aim of the current study was to 1) evaluate the correlation of knee alignment angle measured by goniometer on physical examination with the anatomic angle measured on knee radiographs and 2) to evaluate whether the relationship is confounded by clinical variables that may affect goniometric measurements. Methods: A simple random sample was selected from the MoDEKO (Model for the Diagnosis of Early Knee Osteoarthritis) cohort, cohort of people with knee pain, age 40-79. Knee alignment was measured to the nearest degree by: 1) anatomic-axis on fixed-flexion PA knee radiographs and 2) standardized goniometer assessment on physical examination. Varus was defined as angle < 0, valgus > 0 and 0 o as neutral. Anatomic axis was defined by the intersection of two lines originating from points bisecting the femur and tibia and converging at the centre of tibial spine tips. Inter- and intra-rater reliability of anatomic angle measurements from radiographs were determined by intraclass correlation coefficient (ICC) of two independent assessors. The correlation of radiographic anatomic angle with goniometer measurements was analyzed by linear regression. Western Ontario and McMaster Universities (WOMAC) pain score, body mass index (BMI) and flexion contracture were assessed as potential confounders. Analysis was weighted by stratum sampling weights. Results: Of 120 subjects, 52% were male, with mean (SD) age of 58 (11) years and BMI of 27 (5). The mean (SD) angle measured on PA radiographs and goniometer were 2 (3.6) and 3 (2.3) degrees respectively. Intra- and inter-rater ICC for radiographic measurements were 0.93 and 0.83 respectively. A significant correlation was found between radiographic and goniometer measurements (r = 0.48; P < 0.0001). A model was developed to predict anatomic angle based on goniometer angle: anatomic angle on PA radiographs = 0.410 + 0.749*goniometer angle. WOMAC pain score, BMI and flexion contracture were not significantly associated with PA radiographic angle and did not significantly change the correlation of radiographic and goniometric measurements, and were dropped from the model. Conclusions: In this study, knee alignment assessed by goniometer was significantly correlated with the anatomic axis angle on fixed-flexion PA knee radiographs. Moreover, factors such as pain, BMI and flexion contracture did not confound the relationship of goniometric with radiographic angle measurements. Given the ease of application, goniometric measurements may be preferable to x-ray, although the predictive utility of goniometric alignment measurement will require further assessment in longitudinal studies of knee OA. References: Kraus VB, Vail TP, Worrell T, McDaniel G. A comparative assessment of alignment angle of the knee by radiographic and physical examination methods. Arthritis Rheum 2005;52: 1730–5. Disclosure of Interest: None Declared